EKSPLORASI JENIS DAN PEMANFAATAN TANAMAN FAMILI Zingiberaceae PADA TIGA PASAR CENTRAL TRADISIONAL DI KABUPATEN MERANGIN, JAMBI - Febriani, Widia Putri (Jurnal Biogenerasi, 2025)
Traditional markets in Merangin Regency, Jambi Province, are important places for the distribution and exchange of local biological resources, including plants from the Zingiberaceae family, whose roles and potential are widely recognized. However, empirical data on the specific species traded and their utilization are still very limited. This study aims to explore the diversity of Zingiberaceae family plants sold by traders in three traditional central markets in Merangin Regency, and to identify their various uses. The study was conducted at three traditional central markets in Merangin Regency, namely Pasar Bawah Bangko, Pasar Rakyat, and Pasar Baru Bangko. The type of research used in this study is descriptive qualitative. The results obtained are 11 species of the Zingiberaceae family traded, and their utilization is used as cooking spices, drinks, medicine, and kias (antidote to witchcraft).